Huanying dingyue. Jiang Han Xuebao. Banyue kan. Fudao xuexi Mao zhuxide zhuzuode lilun kanwu
'Welcome to subscribe. Jiang Han journal. Semi-monthly. Coaching the study of theoretical publications written by Chairman Mao.'.